Significant correlations between postoperative outcomes and various limb and component alignment strategies in medial unicompartmental knee arthroplasty: a systematic review - Manuel‐Paul Sava; Alexandra Leica; Isabel Scala; Johannes Beckmann; Michael T. Hirschmann (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose To investigate the correlation between postoperative limb/component alignments and clinical/functional outcomes following medial unicondylar knee arthroplasty (mUKA). Methods Inclusion criteria included peer‐reviewed English‐ or German‐language publications assessing postoperative limb or implant alignment and clinical outcomes of mUKA. Methodological Index for Non‐Randomized Studies (MINORS) was used to assess article quality. Results A total of 2767 knees from 2604 patients were evaluated. Significant correlations were observed between postoperative limb/component alignments and clinical/functional outcomes after mUKA. Inferior outcomes were associated with lower placement and excessive valgus alignment of the tibia component (> 3°). A recommended external rotation of 4°‐5° was identified for the tibia component, with specific cut‐off values for the femoral and tibia components. Conclusions Optimal outcomes in mUKA were associated with a varus coronal limb alignment. The tibia implant component performed well within a specific alignment range. An exact external rotation value was recommended for the tibia component, while internal rotation correlated negatively with the femoral component. Level of evidence IV (level IV retrospective case series were included).